A Note on Trend Growth, Unemployment and Optimal Monetary Policy - Wolfgang Lechthaler; Mewael F. Tesfaselassie (Macroeconomic Dynamics, 2019)
We analyze the implications of trend growth for optimal monetary policy in the presence of search and matching unemployment. We show that trend growth interacts importantly with the inefficiencies stemming from the labor market. Higher trend growth exacerbates the inefficiencies of the labor market and therefore calls for larger deviations from price stability. Our analysis implies that lower trend growth reduces not only the level but also the optimal volatility of the nominal interest rate.
Keywords: 330; trend growth; unemployment; optimal monetary policy; labor market frictions; policy trade-of